1986
DOI: 10.1148/radiology.159.3.3704149
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic microcalcifications: detection with xerography, screen-film, and digitized film display.

Abstract: Pulverized bone specks and aluminum oxide specks were measured by hand into sizes ranging from 0.2 mm to 1.0 mm and then arranged in clusters. These clusters were superimposed on a human breast tissue phantom, and xeromammograms and screen-film mammograms of the clusters were made. The screen-film mammograms were digitized using a high-resolution laser scanner and then displayed on cathode ray tube (CRT) monitors. Six radiologists independently counted the microcalcifications on the xeromammograms, the screen-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 0 publications
1
15
0
1
Order By: Relevance
“…Perisinakis et al [4] demonstrated that the enhancement of image features through post-processing (zooming) of both digitised contact images and geometric magnification mammograms equally improved the visualisation of subtle microcalcifications that are only rarely identified in standard full-field screen-film mammograms. Similar results have been reported by Vyborny et al [11], Smathers et al [14] and Powell et al [15]. These authors also showed that lesion visualisation achieved with geometric magnification mammograms (without the application of further post-processing) was similar to that achieved by electronic magnification and processing of the contact full-field image.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…Perisinakis et al [4] demonstrated that the enhancement of image features through post-processing (zooming) of both digitised contact images and geometric magnification mammograms equally improved the visualisation of subtle microcalcifications that are only rarely identified in standard full-field screen-film mammograms. Similar results have been reported by Vyborny et al [11], Smathers et al [14] and Powell et al [15]. These authors also showed that lesion visualisation achieved with geometric magnification mammograms (without the application of further post-processing) was similar to that achieved by electronic magnification and processing of the contact full-field image.…”
supporting
confidence: 85%
“…If this is the case, zooming offers the advantages that it would not contribute any additional radiation exposure to the patient and, in addition, could decrease the workflow and cost [4,11,14,15]. These authors also showed that lesion visualisation provided by geometrically magnified mammograms (without further post-processing) was similar to Figure 7.…”
Section: Discussionmentioning
confidence: 83%
“…6 Smathers improved the visibility of small objects in images by intensity band-filtering. 7 Chan used unsharpmasking to reduce image noise to improve detection of clustered calcifications. 8 Chan, Hale, and Yin have tested other image processing methods on digitized mammograms with variable results.…”
mentioning
confidence: 99%
“…As non-linear filters like Median filters [9], Wiener filters [15] provide better results by providing better edge preservation and good PSNR values so these are mostly used for biomedical image denoising. Various other filters like unsharp masking [12], digital unsharp masking [7] and spatial band pass filtering [13] have also been used for the contrast enhancement of mammographic images. Soft computing (ICCC-2015) techniques are applied to match the spectra to the type of problem [11].…”
Section: Introductionmentioning
confidence: 99%